Efficiency of Different Solvents in the Extraction of Bioactive Compounds from Plinia cauliflora and Syzygium cumini Fruits as Evaluated by Paper Spray Mass Spectrometry - Vinícius Tadeu da Veiga Correia; Viviane Dias Medeiros Silva; Henrique de Oliveira Prata Mendonça; Ana Luiza Coeli Cruz Ramos; Mauro Ramalho Silva; Rodinei Augusti; Ana Cardoso Clemente Filha Ferreira de Paula; Ricardo Manuel de Seixas Boavida Ferreira; Júlio Onésio Ferreira Melo; Camila Argenta Fante (Molecules, 2023)
Jabuticaba (Plinia cauliflora) and jambolan (Syzygium cumini) fruits are rich in phenolic compounds with antioxidant properties, mostly concentrated in the peel, pulp, and seeds. Among the techniques for identifying these constituents, paper spray mass spectrometry (PS-MS) stands out as a method of ambient ionization of samples for the direct analysis of raw materials. This study aimed to determine the chemical profiles of the peel, pulp, and seeds of jabuticaba and jambolan fruits, as well as to assess the efficiency of using different solvents (water and methanol) in obtaining metabolite fingerprints of different parts of the fruits. Overall, 63 compounds were tentatively identified in the aqueous and methanolic extracts of jabuticaba and jambolan, 28 being in the positive ionization mode and 35 in the negative ionization mode. Flavonoids (40%), followed by benzoic acid derivatives (13%), fatty acids (13%), carotenoids (6%), phenylpropanoids (6%), and tannins (5%) were the groups of substances found in greater numbers, producing different fingerprints according to the parts of the fruit and the different extracting solvents used. Therefore, compounds present in jabuticaba and jambolan reinforce the nutritional and bioactive potential attributed to these fruits, due to the potentially positive effects performed by these metabolites in human health and nutrition.